The argumentative unity of Plato's Parmenides - Horan, David (Trinity College (Dublin, Ireland). Philosophy Department, 2014)
The purpose of this thesis is to make the case that Plato's dialogue Parmenides constitutes an argumentative unity whereby certain philosophic difficulties presented in the first part of the dialogue are resolved by the series of eight arguments that constitute the second part of the dialogue. In order to accomplish this objective we shall first explain, in general terms, the nature and overall structure of the dialogue and the complexities and interpretational possibilities it presents. Having described this we will be able to explain why the reading of the dialogue which we propose to establish and defend may not be universally accepted and indeed is often opposed quite strenuously.
Keywords: Philosophy, Ph.D.; Ph.D. Trinity College Dublin